1992
DOI: 10.1002/ajmg.1320420210
|View full text |Cite
|
Sign up to set email alerts
|

Study of color vision in fragile X syndrome

Abstract: Various theories have been postulated to account for the unusual inheritance pattern observed in the fragile X syndrome. The recent finding of a secondary amplification of the fragile X mutation in the offspring of carrier females [Oberle et al., 1991; Yu et al., 1991] is consistent with a maternal imprinting process. Laird [1987] has proposed that the fragile X mutation blocks complete reactivation of a previously inactivated fragile X chromosome. We have tested whether or not such a localized block extends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…Across several decades and species, it has been reported that KL and Kit are mutually expressed in discrete neuron populations known to be connected; it has thus been hypothesized that the expression pattern of KL-Kit may reflect a role in connectivity ( Keshet et al, 1991 ; Motro et al, 1991 ; Hirota et al, 1992 ; Manova et al, 1992 ). Consistent with such a function, case reports have implicated inactivating Kit mutations with disorders of the central nervous system ( Telfer et al, 1971 ; Finucane et al, 1991 ; Funderburk and Crandall, 1974 ; Lacassie et al, 1977 ; Kilsby et al, 2013 ; Figure 1—figure supplement 1C ). Clinical phenotypes include developmental delay, ataxia, hypotonia, intellectual disability, deafness, and autism spectrum disorder.…”
Section: Introductionsupporting
confidence: 59%
“…Across several decades and species, it has been reported that KL and Kit are mutually expressed in discrete neuron populations known to be connected; it has thus been hypothesized that the expression pattern of KL-Kit may reflect a role in connectivity ( Keshet et al, 1991 ; Motro et al, 1991 ; Hirota et al, 1992 ; Manova et al, 1992 ). Consistent with such a function, case reports have implicated inactivating Kit mutations with disorders of the central nervous system ( Telfer et al, 1971 ; Finucane et al, 1991 ; Funderburk and Crandall, 1974 ; Lacassie et al, 1977 ; Kilsby et al, 2013 ; Figure 1—figure supplement 1C ). Clinical phenotypes include developmental delay, ataxia, hypotonia, intellectual disability, deafness, and autism spectrum disorder.…”
Section: Introductionsupporting
confidence: 59%
“…Across several decades and species, it has been reported that KL and Kit are mutually expressed in discrete neuron populations known to be connected; it has thus been hypothesized that the expression pattern of KL-Kit may reflect a role in connectivity [5][6][7][8]. Consistent with such a function, case reports have implicated inactivating Kit mutations with disorders of the central nervous system (References [9][10][11][12][13] and Figure S1C). Clinical phenotypes include developmental delay, ataxia, hypotonia, intellectual disability, deafness, and autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 92%